Validity of a 5-meter multiple shuttle run test for assessing fitness of women field hockey players - Boddington, M. K.; Lambert, M. I.; Waldeck, M. R. (The Journal of Strength and Conditioning Research, 2004)
The aim of this study was to establish validity of a 5-m multiple shuttle test (5-m MST) using indirect (criterion and construct) and direct measures of performance. For criterion validity, comparisons were made between data from established fitness tests and a 5-m MST. Construct validity was determined by comparing results from a 5-m MST with subjects of different playing abilities. Direct validity was determined by comparing values attained from a 5-m MST with data from a time-motion study of field hockey. For criterion validity, the strongest relationship existed between the 20-m MST (42.7 ± 7.1 ml·kg-1·min-1) and total distance from the 5-m MST (650.9 ± 59.2 m; r = 0.92). For construct validity, regional representative players covered more distance than club-level players (689.9 ± 46.6 m vs. 661.1 ± 31.0 m; p < 0.01). For direct validity, the highest correlation was found between total distance from the 5-m MST (706.0 ± 37.5 m) and mean displacement during matches (61.0 ± 6.0 m; r = 0.74). It was concluded that the 5-m MST had both indirect and direct validity for the fitness assessment of field hockey players. The data obtained from the 5-m MST directly relates to the physical fitness of the players during competition.